1998
DOI: 10.1097/00019606-199808000-00004
|View full text |Cite
|
Sign up to set email alerts
|

RNA From Decades-Old Archival Tissue Blocks for Retrospective Studies

Abstract: The validity of molecular studies using DNA and RNA extracted from decades-old formalin-fixed and paraffin-embedded tissue blocks has been demonstrated. The quality and usability of DNA and RNA from archival tissues are modified by various factors, such as the fixative, the fixation time, and the postmortem time. However, in contrast to DNA, there are no comprehensive studies quantitatively addressing the feasibility of RNA from old (more than 10 years) archival samples. This study examined the integrity of RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 27 publications
1
62
0
Order By: Relevance
“…Although these methods can yield RNA suitable for PCR amplification and analysis, the effect of prolonged formalin fixation has not been well studied. Previous studies that have examined this issue in a controlled manner have used fixation times of Յ24 hours (3,5,24,34,35). Although this duration may be suitable for small tissues obtained in some hospital settings, it is likely shorter than those typically used for larger specimens or those obtained in outpatient settings or in mail-in biopsy services.…”
Section: Discussionmentioning
confidence: 99%
“…Although these methods can yield RNA suitable for PCR amplification and analysis, the effect of prolonged formalin fixation has not been well studied. Previous studies that have examined this issue in a controlled manner have used fixation times of Յ24 hours (3,5,24,34,35). Although this duration may be suitable for small tissues obtained in some hospital settings, it is likely shorter than those typically used for larger specimens or those obtained in outpatient settings or in mail-in biopsy services.…”
Section: Discussionmentioning
confidence: 99%
“…Although RNA can be extracted from such tissue (Rupp & Locker 1988), extensive degradation can occur before (Mizuno et al 1998) or during (Klimecki et al 1994) the formalin fixation process. Furthermore, formalin fixation generates cross-links between nucleic acids and proteins and covalently modifies RNA, making subsequent RNA extraction, RT and quantification analysis problematic (Masuda et al 1999).…”
Section: Template Preparationmentioning
confidence: 99%
“…A short time interval between sampling and fixation also seems to be important for efficient amplification Mizuno et al, 1998). The needle liver biopsies analyzed in the present study were immediately fixed in formalin after being taken, and the fixation time was no longer than 24 hours.…”
Section: Soguero Et Almentioning
confidence: 99%
“…Recently, several authors reported that HCV-RNA sequences may also be recovered and amplified by RT-PCR from formalin-fixed, paraffin-embedded (FFPE) liver tissue (Abe et al, 1998;Akyol et al, 1992;Bresters et al, 1992;Edamato et al, 1996;el-Batanony et al, 1994;Guerrero et al, 1997), even when stored for more than 20 years (Mizuno et al, 1998;Soguero et al, 1999). This approach may be valuable for retrospective studies when frozen liver tissue or serum are not available.…”
mentioning
confidence: 99%
See 1 more Smart Citation